Consumers’ second-hand clothing purchase intention: integrating TPB, face consciousness and past purchase experience - Zhou, Qi; Ji, Xiaofen; Li, Nan; Zhou, Liyuan (Frontiers in Psychology, 2025)
This study establishes an integrated theoretical framework to comprehensively examine the factors influencing Chinese consumers’ second-hand clothing (SHC) purchase intention. Utilizing a randomly sampled dataset of 654 Chinese consumers, structural equation modeling (SEM) was conducted using AMOS software. The analysis demonstrates that our integrated model exhibits superior predictive power for SHC purchase intention compared to existing frameworks, achieving statistically satisfactory results. The findings provide support for all hypothesized relationships among the theoretical constructs, while the significant mediating effects of the proposed mediators were also confirmed. Notably, invariance tests revealed the moderating effect of past purchase experience.